Burkholderia cepacia infection in a non-cystic fibrosis patient: an arcane presentation. Issue 4 (15th April 2021) - Ibrahim, Sufyan; Madigubba, Haritha; N, Himanshu Y.; Chawla, Kiran
Abstract : Introduction. Burkholderia cepacia is an aerobic, Gram-negative bacillus, which exhibits innate resistance to multiple antibiotics and disinfectants. Although it is a chronic colonizer of the respiratory tract, it may rarely present with fatal necrotizing pneumonia-like features in immunosuppressed individuals, as those with chronic granulomatous disease, or patients with significant pulmonary compromise, like cystic fibrosis. Case Presentation. A 76-year-old male presented with complaints of breathlessness, cough with mucoid expectoration and fever for 3 days. He had a history of coronary artery disease, chronic obstructive pulmonary disease (COPD), diabetes mellitus and hypertension, under treatment. Pulmonary function tests were suggestive of very severe obstruction (FEV1/FVC was 55 %). So, clinical diagnosis of acute exacerbation of COPD was established. Sputum culture grew B. cepacia . The patient was treated with ceftazidime and meropenem along with inhalational bronchodilators and steroids, and showed symptomatic response to therapy. Conclusion. There is paucity of the literature describing B. cepacia as a potential cause for acute exacerbations in relatively common clinical conditions, such as COPD. This case report highlights the speculation of this rare possibility, thereby alerting a clinician dealing with such cases.